Study of Physico-chemical Parameters of Ground Water Quality: A Geographical Analysis of Varanasi District - Prajapati, Rajesh; Bilas, Ram (National Geographical Journal of India, 2022)
The quality of ground water is deteriorating very drastically during recent decades due to industrialization and urbanization. This is the serious problem now a day required immediate attention for the appraisal of the quality of water for drinking /domestic purposes. To assess the quality, 55 ground water samples were collected from the different places of the study area. The drinking water quality analysis have been made through the assessment pH, EC, Chloride, Total Hardness, Sodium, Potassium, Calcium, Magnesium, Sulphate, Nitrate and Fluoride. A systematic calculation of the water samples has also been carried out between different analysed physic- chemical parameters of study area. This work has been carried out mainly with objectives to know the water quality characteristics and the status of ground water quality condition for drinking water suitability of the area under study.